2008
DOI: 10.4013/nbc.20083.06
|View full text |Cite
|
Sign up to set email alerts
|

Efetividade de Áreas Protegidas (APs) na conservação da qualidade das águas e biodiversidade aquática em sub-bacias de referência no rio das Velhas (MG)

Abstract: Palavras-chave: unidades de conservação, macroinvertebrados bentônicos, bacia hidrográfica, planejamento e gestão ambiental. AbstractThe creation of protected areas is one of the most important methods for the preservation of the biodiversity. It does not necessarily mean that the creation of these areas will guarantee the proper conservation of all biodiversity. It is necessary to evaluate the site, the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 17 publications
1
11
0
2
Order By: Relevance
“…The observed differences in the rarefied richness, the Shannon Diversity Index, Evenness, and composition of fauna inside and outside of the PA supported this assertion. In addition, we observed that the dominance of Chironomus, which is a bioindicator of impacted sites (high organic matter and eutrophication) ( The highest rarefied richness observed in the streams sections located inside the parks is an indication that the protected areas help to maintain the environmental integrity of the sites and favors this condition (Paz et al, 2008;Caldeira et al, 2013). Bueno et al (2003) suggests that the high richness of organisms is related to good conditions of integrity, suggesting availability of habitats, food sources and niches to be occupied, supporting the survival of organisms.…”
Section: Discussionmentioning
confidence: 83%
“…The observed differences in the rarefied richness, the Shannon Diversity Index, Evenness, and composition of fauna inside and outside of the PA supported this assertion. In addition, we observed that the dominance of Chironomus, which is a bioindicator of impacted sites (high organic matter and eutrophication) ( The highest rarefied richness observed in the streams sections located inside the parks is an indication that the protected areas help to maintain the environmental integrity of the sites and favors this condition (Paz et al, 2008;Caldeira et al, 2013). Bueno et al (2003) suggests that the high richness of organisms is related to good conditions of integrity, suggesting availability of habitats, food sources and niches to be occupied, supporting the survival of organisms.…”
Section: Discussionmentioning
confidence: 83%
“…The conservation of the Brazilian freshwater ecosystems and their biodiversity depends in part on the establishment of conservation units that encompass entire hydrographic basins, and that are based on studies of their ecological and biological conditions (PAZ et al, 2008). Knowledge about the health status of aquatic ecosystems and the value of the potential services that they can provide to humans allows optimal and sustainable use of the available resources (CONSTANZA et al, 1997).…”
mentioning
confidence: 99%
“…Neste âmbito, as bacias hidrográficas já vêm sendo alvo de planos de gerenciamento e dos mais variados estudos acerca de seus condicionantes naturais, vulnerabilidades e gerenciamento Carneiro et al, 2008;Horn e Silveira, 2015;Pereira Neto e Fernandes, 2015), e não são escassos os estudos onde as proposições teóricas sobre gerenciamento de recursos hídricos são aplicadas em sub-bacias e microbacias hidrográficas (Mendonça, 1999;Paz et al, 2008;Aguiar et al, 2015).…”
Section: Introductionunclassified